# WRITE the rule as an equation in terms of x for each of the function table y=y-6?

### 3 Answers

Relevance

- ComoLv 78 months ago
Have looked everywhere but not an x in sight !

If

y = x - 6

x = y + 6

- Log in to reply to the answers

- 8 months ago
there is no x in your equation.

y = y - 6

resolves to an always false case since if you subtract y from both sides you get:

0 = -6

Which is not true.

- Log in to reply to the answers

- llafferLv 78 months ago
there is no x in your equation.

y = y - 6

resolves to an always false case since if you subtract y from both sides you get:

0 = -6

Which is not true.

- Log in to reply to the answers

Still have questions? Get answers by asking now.